PENERAPAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING PADA MATERI ANALISIS DATA MENGGUNAKAN MICROSOFT EXCEL UNTUK MENINGKATKAN KREATIVITAS DAN HASIL BELAJAR SISWA - Nur Sa’ida Kismurdiani; Harits Ar Rosyid; Suparman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study focuses on enhancing students' creativity and learning outcomes through the implementation of the Culturally Responsive Teaching (CRT) approach in the topic of data analysis using Microsoft Excel in class VIII-J of SMP Negeri 19 Malang. The main problem faced by students is the low understanding of Informatics, particularly data analysis, which is often perceived as abstract and difficult to grasp. This research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, which consists of two cycles. Data were collected through observation and learning outcome tests. The results showed an improvement in student creativity from the "fair" category (58.61%) in the pre-cycle to "excellent" (82.77%) in the second cycle. Furthermore, learning mastery increased from 31.25% in the pre-cycle to 90.63% in the second cycle. The implementation of CRT, which connects learning content with local culture such as traditional foods and regional products, was able to create meaningful and relevant learning experiences and increase students' active participation. This research demonstrates that CRT is an effective approach to improving the quality of Informatics learning, particularly in fostering student creativity and understanding of data-based material.